The effect of two bleaching agents on the phosphate concentration of the enamel evaluated by Raman spectroscopy: An ex vivo study - Sokkalingam Mothilal Venkatesan; Gopal Shankar Narayan; Anil Kumar Ramachandran; Rajamani Indira (Wolters Kluwer Medknow Publications, 2012)
Aim : The aim of this ex vivo study was to evaluate the effect of in-office bleaching agents,-35% and 38% hydrogen peroxide containing bleaching agents, on the phosphate concentration of the enamel evaluated by Raman spectroscopy. Materials and Methods : Forty noncarious, craze-free human maxillary incisors, extracted for periodontal reasons, were used in this study. Baseline Raman spectra from each specimen were obtained before the application of the bleaching agent to assess the phosphate content present in the teeth. The teeth were divided into two groups: Group A - bleached with pola office bleach (35% hydrogen peroxide, potassium nitrate) (light activated). Group B - bleached with opalescence Xtra bleach (38% hydrogen peroxide potassium nitrate and fluoride) (chemical activated). After the bleaching procedure, the treated specimens were taken to obtain Raman spectra to assess the phosphate loss after bleaching treatment. Results : The results showed that the chemically activated bleaching agent showed less phosphate loss when compared with the light activated bleaching agent. Conclusion : Within the limitations of this study, it can be concluded that the chemically activated bleaching agent showed minimal phosphate loss when compared to light activated bleaching agent. The chemically activated bleaching agent was better than the light activated bleaching agent when values were evaluated statistically.